Antisolvent diffusion-induced growth, equilibrium behaviours in aqueous solution and optical properties of CH3NH3PbI3 single crystals for photovoltaic applications1. Issue 104 (11th November 2015) - Zhou, Huawei; Nie, Zhonghao; Yin, Jie; Sun, Yuanwei; Zhuo, Hongyan; Wang, Daqi; Li, Dacheng; Dou, Jianmin; Zhang, Xianxi; Ma, Tingli
<x xml:space="preserve">Abstract</x> Antisolvent diffusion-induced growth, equilibrium behaviours in aqueous solution and optical properties of CH3NH3PbI3 single crystals.